RISK FACTORS AND PREVENTIVE MEASURES FOR DIABETES AMONG YOUTH (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Sugary diabetes globally serious medical-social problem considered , last in years youth between this of the disease meeting frequency noticeable at the level exceed Metabolic of processes violation , wrong nutrition , exercise marriage style and psychoemotional tensions sugary diabetes development main danger factors as being considered . At a young age started diabetes disease heart and blood vein system , kidneys , vision members and nerve system to damage take come early disability and death the risk increases . This in the article sugary diabetes epidemiological status , youth between to meet impact provider main danger factors , clinical symptoms , diagnosis methods and effective prevention measures scientific basics illuminated .